Edukasi Pemanfaatan Gedi Merah Sebagai Obat Dislipidemia - Handayani, Tien Wahyu; Tandi, Joni; Alaydus, Syafika; Rajadenda, Afwa Al; Sujati, Ni Wayan (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
Indonesia has 143 million hectares of tropical forest which grows 80% of the world's medicinal plants. It is estimated that 25 thousand to 30 thousand plants can be used as medicine. One of these plants is red gedi or Abelmoschus manihot. Apart from having a delicious taste, red gedi leaves also contain many polyphenols, flavonoids, tannins, vitamin A, iron, fiber, folic acid, petroleum, methanol, collagen, vitamin C and several other nutrients which can be useful as a medicine for dyslipedemia. This activity aims to educate the community in Sejahtera Village, Palolo District, Sigi Regency about the use of red gedi as a medicine for dyslipidemia. This service uses lecture methods and distributing brochures. Presentation of the level of public understanding of the benefits of red gedi is 96%, public understanding of dyslipidemia is 95%, and people's skills in processing red gedi into food and drinks that are good for health are 100%.